Discharge Planning Terhadap Tingkat Kepuasan Pasien di Rumah Sakit - Rini Fahriani Zees; Hendrik Prayitno Luawo; Rahmatiya Thalib (Poltekkes Kemenkes Gorontalo, 2021)
One form of services provided to improve the quality of services such as discharge planning. January 2017 there are 3 most prominent diseases including thypoid patients who junmlah 21 people, gastritis patients who numbered 21 people and diabetes melitus patients amounted to 15 people. Knowing the effectiveness of discharge planning with the level of patient satisfaction in RSUD Toto Kabila Bone Bolango District.This type of research is quasi experiment design where in this design observation (pretest and posttest). The population is the patient in the internal room who suffer from typoids, gastritis and diabetes mellitus while doing research. The sample in this research use purposive sampling technique. Independent variable in this research discharge planning and dependent variable is patient satisfaction.The results showed the results of t test the effectiveness of discharge planning with the level of patient satisfaction in RSUD Toto Kabila Bone Bolango District indicated by asymp.sig value of 0.000, this value is smaller than significant value 0.05.The conclusions of this study were Patient satisfaction level before discharge planning was not satisfied 23 people (85%) and satisfied 4 people (15%), The level of patient satisfaction after discharge planning was increased to 23 people (85%) and the dissatisfaction was reduced to 2 people (7%).